Simulation of Asynchronous Starting of Converter Tilting Mechanism Reducer based on LS-DYNA and Hyper Mesh - Ren Xueping; Yang Songtao (Jixie chuandong)
Aiming at the brakes open out of sync phenomenon of 210 t converter tilting mechanism in a steel plant,to study the influence of contact-impact on the gear strength under this working condition,the geometry entity model of the reducer is set up in Pro / E,and it is imported into the software of Hyper Mesh to built the finite element solving model,and the solving is carried out by using the explicit dynamics solver LS-DYNA.According to the results,a conclusion can be drawn that the impact stress of the pinion starting later is far less than that of three other pinions,when the gears contact without clearance and brakes open out of sync.At the same time,the result verifies the conclusion that the gear contact impact stress increases with increasing of the velocity difference between the gears and the maximum impact stress of gear occurs in tooth root in the middle of tooth width.